2019
DOI: 10.1177/0309324719835706
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different helmet shell configurations on the protection against head trauma

Abstract: Head trauma following a ballistic impact in a helmeted head is assessed in this work by means of finite element models. Both the helmet and the head models employed were validated against experimental high-rate impact tests in a previous work. Four different composite ply configurations were tested on the helmet shell, and the energy absorption and the injury outcome resulting from a high-speed impact with full metal jacket bullets were computed. Results reveal that hybrid aramid–polyethylene configurations do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…Even though a turban leaves 38% of the cranial surface area unprotected, that area appears to be significantly underrepresented as an impact zone. While there are modelling studies that consider the protective capability of helmets on head trauma, for example, from ballistic impact [113] or blunt impact while cycling [114], only one modelling study has been located that relates to impacts in sports. A French study with 1920 simulations using multiple rider postures as well as horse movements found three main impact areas (frontal, parieto-occipital, and temporospatial) with the greatest force exerted on the frontal area [112].…”
Section: Protective Potential Of Turbansmentioning
confidence: 99%
“…Even though a turban leaves 38% of the cranial surface area unprotected, that area appears to be significantly underrepresented as an impact zone. While there are modelling studies that consider the protective capability of helmets on head trauma, for example, from ballistic impact [113] or blunt impact while cycling [114], only one modelling study has been located that relates to impacts in sports. A French study with 1920 simulations using multiple rider postures as well as horse movements found three main impact areas (frontal, parieto-occipital, and temporospatial) with the greatest force exerted on the frontal area [112].…”
Section: Protective Potential Of Turbansmentioning
confidence: 99%
“…The helmet shell is the most external part and constitutes the principal structural element of the EOD helmet. It is made of composite based on aramid fiber, which is widely used in the field of personal protection [21,22,[28][29][30][31][32] due to the excellent resistance to weight ratio. Helmet shell thickness is 4 mm.…”
Section: Helmet Assembly Modelmentioning
confidence: 99%